The effect of lavender aromatherapy on the frequency of decreasing emesis gravidarum in the 1st trimester pregnant women - Hanik Khairun Nisa; Wahyu Ernawati (Institute of Computer Science (IOCS), 2023)
Emesis gravidarum is a complaint that is often experienced by pregnant women in the first trimester of pregnancy. This happens because it is caused by various changes in a woman's body during pregnancy. One of the occurrences of emesis gravidarum is because there is an increase in the HCG hormone. Emesis gravidarum that is not treated immediately will result in hyperemesis gravidarum which will be dangerous for the pregnant woman. The aim of this research was to determine the effect of Lavender aromatherapy on reducing emesis gravidarum in first trimester pregnant women at Peaktik Mandiri Midwife (PMB) Choirul Mala. This type of research is one group pre-post test design. The population in this study were all pregnant women at PMB Choirul Mala, namely 30 people. Sampling in this study used a purposive sampling technique so that 15 respondents were obtained. Collecting data in this study using a questionnaire. Analysis of research data includes univariate analysis and bivariate analysis using the Wilcoxon test. The results of the study showed that before being given therapy, most of the 60% of respondents had severe levels of nausea and vomiting and after being given therapy, the majority of 66.7% of respondents had mild levels of nausea and vomiting. Based on the results of statistical analysis, it was found that the p value = 0.000, meaning that there was an effect of providing lavender aroma therapy on reducing the frequency of emessis gravidarum in the first trimester of pregnancy. It can be concluded that lavender aroma therapy has proven to be effective in reducing the frequency of nausea and vomiting in pregnant women.